Pola Pengadaan Obat di 4 Apotek Jaringan Wilayah Bumi Serpong Damai (BSD) Tangerang Selatan - Ismaya, Nurwulan Adi; Pratiwi, Rita Dwi; Sari Indah, Fenita Purnama; Aulia, Gina; Sumarwati, Sumarwati (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2022)
Pharmacies are an inseparable part of the drug distribution chain until it reaches the patient. However, patients often hear complaints about the availability of drugs in pharmacies because sometimes there are drug shortage. The aim of this study was to identify the drug procurement pattern in four network pharmacies in the Bumi Serpong Damai (BSD) area in 2019. A retrospective study of four network pharmacies in the Bumi Serpong Peace (BSD) area of South Tangerang was carried out. A total of 8,959 samples were obtained by census from procurement documents of all drugs sold beginning in 2019. (A, B, C, and D pharmacies). The ABC and VEN methods were used in this study. The information gathered includes the name of the drug, the unit, the manufacturer's name, the creditor's name, and the amount and selling price. During 2019, four pharmacies had a total of 2,876 medicinal items of pharmacy A, 1,918 medicinal items of pharmacy B, 1,939 medicinal items of pharmacy C, and 2,226 medicinal items of pharmacy D, with a total drug expenditure of pharmacy A Rp.2,649,438;pharmacy B Rp.683,389,661; pharmacy C Rp. 881,540,329; and pharmacy D Rp. 1,245,520,143. Based on the findings of the study, it is possible to conclude that the four pharmacies have the most drugs in the essential category based on the VEN analysis. However, based on the Pareto ABC analysis, there are still many drugs in four network pharmacies in the BSD Region that fall into the Pareto C category, necessitating further investigation of the procurement.